Analisis Tingkat Kerusakan Produk Untuk Kelancaran Proses Produksi Pada Pabrik Tepung Tapioka PT. Gunung Sugih - Setiawan, Adang; Widodo, Deny Edy (Jurnal Manajemen DIVERSIFIKASI, 2023)
Quality control during the production process really needs to be done to determine the quality level of the product being processed and the actions that need to be taken if there are deviations, changes, or contamination of the product during processing. The quality control system carried out at PT. Mount Sugih in Bumi Ratu Nuban, Central Lampung Regency is still lacking because so far only one employee has served as part of quality control and equipment is still lacking and there is no quality checking laboratory. The aims of this research are: 1) to find out whether the level of product damage is still within the tolerance limit, 2) to find out what type and amount of damage is the most and the order of the types of damage that occur, and 3) to find out what factors which causes damage to tapioca flour products. This type of research is a qualitative research with an analytical observational design. Data collection techniques were carried out by interview and observation. The analysis tool uses Control Chart, Pareto Chart, and Cause and Effect Diagram (Fishbone). The results of this study indicate that based on the C Chart diagram the amount of damage that occurs is still within the tolerance limit between the lower limit of 0.99% (LCL) and the upper limit of 5.22% (UCL). The number of product defects based on the order of number is the highest defect in product color (26.16%), moisture content (23.14%), musty aroma (20.56%), coarser texture (17.56%) and object contamination foreign (12.5%). The factors that affect the damage of tapioca flour are mostly related to unskilled labor and lack of quality control personnel as well as other causes such as raw materials and the environment.